Migrants Selection and Replacement in Distributed Evolutionary Algorithms for Dynamic Optimization - Bravo Garcia, Yesnier; Luque-Polo, Gabriel Jesús; Alba-Torres, Enrique (Springer, 2013)
Many distributed systems (task scheduling, moving priorities, changing mobile environments, ...) can be linked as Dynamic Optimization Problems (DOPs), since they require to pursue an optimal value that changes over time. Consequently, we have focused on the utilization of Distributed Genetic Algorithms (dGAs), one of the domains still to be investigated for DOPs. A dGA essentially decentralizes the population in islands which cooperate through migrations of individuals. In this article, we analyze the effect of the migrants selection and replacement on the performance of the dGA for DOPs. Quality and distance based criteria are tested using a comprehensive set of benchmarks. Results show the benefits and drawbacks of each setting in dynamic optimization.
Keywords: Algoritmos genéticos; Dynamic Optimization; Experimental Analysis; Parallelism; Distributed Evolutionary Algorithm